(untitled) (Ameghiniana, 2014)
The typification ofthree species of Hausmannia described by E. Feruglio in 1937 is discussed. The original specimens are lodged at the Museo Argentino de Ciencias Naturales "B. Rivadavia", Paleobotany Division (BA Pb). Lectotype specimens are selected or confirmed for Hausmannia papilio and Hausmannia de-ferrariisii. The holotype and paratype of Hausmannia patagonica are also considered.